2016
DOI: 10.2136/sssaj2016.04.0129
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Antimonate by Gibbsite: Reversibility and the Competitive Effects of Phosphate and Sulfate

Abstract: Antimony (sb) is a potential environmental contaminant of emerging concern that occurs in soils in the sb(V) oxidation state as the antimonate species sb(OH) 6 -. In soils, metal oxyhydroxides play an important role in the immobilization of contaminants and in restricting bioaccessibility. One such mineral is gibbsite, which bears the reactive aluminol surface functional group. Both inner-and outer-sphere surface complexation mechanisms have been inferred from conflicting sb(V) adsorption findings involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 63 publications
3
6
0
Order By: Relevance
“…The adsorption decreased steeply from pH 6.5 to 9 from a value of about 80% to below detectable levels. The behavior of the Sb (V)-hematite adsorption envelope followed a similar trend to other oxide minerals [10,33,40]. For example, Leuz et al (2006) [10] found that between pH 3 and 6, about 96% of Sb (V) was adsorbed on goethite at ionic strength values of 0.1 and 0.01 M KCl.…”
Section: Adsorption Envelope and Surface Complexation Modelingsupporting
confidence: 60%
See 2 more Smart Citations
“…The adsorption decreased steeply from pH 6.5 to 9 from a value of about 80% to below detectable levels. The behavior of the Sb (V)-hematite adsorption envelope followed a similar trend to other oxide minerals [10,33,40]. For example, Leuz et al (2006) [10] found that between pH 3 and 6, about 96% of Sb (V) was adsorbed on goethite at ionic strength values of 0.1 and 0.01 M KCl.…”
Section: Adsorption Envelope and Surface Complexation Modelingsupporting
confidence: 60%
“…In general, chemical models that produce V Y values less than 20 are deemed acceptable, although the desired result is to identify a chemical model that generates the smallest value of V Y , and is supported by a mechanistic interpretation of the experimental ATR-FTIR data. Several surface complexation reactions have been proposed to describe Sb retention at variable-charge surface functional groups [39][40][41][42]. Commonly, these include inner-sphere monodentate or bidentate and outer-sphere surface complexes, alone or in combination.…”
Section: Surface Complexation Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, formation of inner‐sphere complexation was highly thermodynamically stable that is responsible for the irreversible adsorption observed in the environment. [ 29 ] In such inner‐sphere complexation configuration, surface states are strongly occupied by the adsorbed ions and consequently they are no longer available for water oxidation. Due to this unique adsorption behavior, although arranging a condition with trace concentration (~μM) of Zn(II) would not elaborate any superior performance afterword, it would be an excellent opportunity to quantify the concentration of surface states, which is barely reported in any literature.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that the decrease of the adsorbent's zeta potential aer adsorption of anions is related to an inner-sphere complexation in which chemical bond is formed between Sb(OH) 6 À and adsorbent surface. 18,48,49 In contrast, an outer-sphere complexation reaction is based on physical interaction between the anion and positively charged adsorbent surface and does not change the surface charge of the adsorbent. Our results show that the zeta potential decreases drastically aer Sb(V) adsorption indicating an inner-sphere complexation reaction.…”
Section: Adsorption Properties Of the Zro 2 Bersmentioning
confidence: 99%